1995
DOI: 10.4102/sajip.v21i1.583
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationship between the work experience of distance education students, job satisfaction, andacademic achievement

Abstract: In terms of the cooperative education strategy of technikons, students are expected to do subject-relevant work in the industry/commerce to gain practical experience. The degree of subject-relevant work performed by 166 distance education students, and how this is related to their academic performance, was investigated. It was found that in contrast to older Afrikaans- and English-speaking male students, it was mainly students who speak a black language who do not gain subject-relevant work experience, have mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In line with this, Welman and Basson (1995) investigated the relationship between the degree of subject-related work performed by 166 distance education students and their academic performance. Their study found that in comparison with older, male, Afrikaans-and English-speaking students, African-language speakers tended not to gain subject-related experience, experienced less job satisfaction and received lower marks for the third-year subject, Organisational Behaviour.…”
Section: Perspectives On Co-operative Educationmentioning
confidence: 99%
“…In line with this, Welman and Basson (1995) investigated the relationship between the degree of subject-related work performed by 166 distance education students and their academic performance. Their study found that in comparison with older, male, Afrikaans-and English-speaking students, African-language speakers tended not to gain subject-related experience, experienced less job satisfaction and received lower marks for the third-year subject, Organisational Behaviour.…”
Section: Perspectives On Co-operative Educationmentioning
confidence: 99%
“…The MSQ is a rating scale designed to measure job satisfaction, specifically in terms of implementation of ability, achievement, activity, advancement, authority, organisational policies and practices, compensation, co-workers, creativity, independence, moral values, recognition, responsibility, security, social service, social status, supervision (human relations and technical), variety, and working conditions. The short version of the MSQ consists of 20 questions that measure the extent to which employees are satisfied with various aspects of their current job (Welman & Basson, 1995).…”
Section: Methods Participantsmentioning
confidence: 99%
“…The questionnaire used to measure the 11th organisational dimension (job satisfaction) was the short version of the Minnesota Job Satisfaction Questionnaire (MSQ) developed by Weiss, Dawis, England and Lofquist (Welman & Basson, 1995). The MSQ is a rating scale designed to measure job satisfaction, specifically in terms of implementation of ability, achievement, activity, advancement, authority, organisational policies and practices, compensation, co-workers, creativity, independence, moral values, recognition, responsibility, security, social service, social status, supervision (human relations and technical), variety, and working conditions.…”
Section: Methods Participantsmentioning
confidence: 99%